RETRACTED: Invasion of trophoblast cell lines is inhibited by miR-93 via MMP-2. (May 2017) - Pan, Qiong; Niu, HuiYuan; Cheng, LongFei; Li, XiaoQiong; Zhang, QiGang; Ning, Ying
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal(https://www.elsevier.com/about/our-business/policies/article-withdrawal) . This article has been retracted at the request of the Editors. Western Blots from Figure 2A are similar to Western Blots from Figures 3A, D of Reference [1], Figures 3A, D of Reference [2], Figure 1A of Reference [3], Figures 2A, D of Reference [4], Figures 1A, B of Reference [5], Figures 2A, B of Reference [6], Figures 2A, B of Reference [7] and Figures 2A, B of Reference [8]. Panels of Figure 3A are similar to panels of Figure 2B of Reference [1], Figure 3A of Reference [8] and Figures 3E, F of Reference [9]. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process. References [1] Yongfang Wang, Lianhong Xu, Lixin Jiang, Biochemical and Biophysical Research Communications (BBRC) 458 (2015) 714-719http://dx.doi.org/10.1016/j.bbrc.2015.02.033 . [2] Hong Zhu, Mei-hua Miao, Xue-qiang Ji, Jun Xue, Xue-jun Shao, BBRC 459 (2015) 340-345http://dx.doi.org/10.1016/j.bbrc.2015.02.116 . [3] Mingchen Shao, Yiwei Geng, Peng Lu, Ying Xi, Sidong Wei, Liuxing Wang, Qingxia Fan, Wang Ma, BBRC 464 (2015) 1309-1313http://dx.doi.org/10.1016/j.bbrc.2015.07.128 . [4] Xiangrui Meng, Peng Lu, Qingxia Fan, BBRC 470 (2016) 187-191http://dx.doi.org/10.1016/j.bbrc.2016.01.025 . [5] Junzhao Wu, Peng Yuan, Qixin Mao, Peng Lu, Tian Xie, Hanzhao Yang, Chengzheng Wang, BBRC 478 (2016) 274-278http://dx.doi.org/10.1016/j.bbrc.2016.07.031 . [6] Wenxian Cui, Yuanguo Li, Keqing Xu, Guijin Chen, Xiaoqun Lu, Qiuqin Duan, Zhirong Kang, BBRC 479 (2016) 901-906http://dx.doi.org/10.1016/j.bbrc.2016.09.076 . [7] Mingjun Bi, Wei Chen, Hongmei Yu, Jinxiu Wang, Fang Ding, Dong Jing Tang, Cuiyan Tang, BBRC 480 (2016) 369-374http://dx.doi.org/10.1016/j.bbrc.2016.10.055 . [8] Wenjun Tian, Guanghai Wang, Yiqing Liu, Zhenglan Huang, Caiqing Zhang, Kang Ning, Cuixiang Yu, Yajuan Shen, Minghui Wang, Yuantang Li, Yong Wang, Bingchang Zhang, Yaoran Zhao, BBRC 485 (2017) 35-40http://dx.doi.org/10.1016/j.bbrc.2017.02.005 . [9] Youcheng Xiu, Zan Liu, Shunyao Xia, Chengjun Jin, Huaifu Yin, Weiming Zhao, Qiong Wu, PLoS ONE 9(10) (2014) e109734https://doi.org/10.1371/journal.pone.0109734 .